Intravenous fluid Considerations in the Resuscitation of a Head Injured Patient - Singh, Prakash (Indian Journal of Neurotrauma, 2005)
Resuscitation of the head injured patients with shock poses a dilemma to the treating neurosurgeon. Whereas achieving hemodynamic stability is the objective in shock and in head injury, there is apprehension that aggressive fluid resuscitation may lead to aggravation of brain edema, especially if fluids used in resuscitation are hypoosmolar. Instituting cerebral decongestants such as mannitol, frusemide to treat raised intracranial pressure may cause hypotension due to obligatory diuresis. This review article examines the literature on the resuscitation of head injured patient and closely looks into the suitability of various intravenous fluids available today for this emergency situation.
Keywords: cerebral edema; colloids; crystalloids; head injury; intravenous fluids